Digital Gamification in Islamic Religious Education Learning: Systematic Literature Review - Haqjaya, Bima Purwidya (Blantika: Multidisciplinary Journal, 2026)
The rapid development of digital technology in the era of Society 5.0 has encouraged innovation in education, including Islamic Religious Education (PAI). However, PAI learning is still frequently dominated by conventional approaches that reduce student engagement and learning motivation. In this context, digital gamification has emerged as an innovative strategy capable of creating more interactive, enjoyable, and student-centered learning experiences. This study aims to analyze the application, forms, and impacts of digital gamification in Islamic Religious Education learning through a systematic literature review approach. The research employed the PRISMA framework to identify, screen, evaluate, and synthesize relevant studies published between 2020 and 2026. Literature data were collected through Google Scholar using Publish or Perish software, resulting in 32 selected articles that met the inclusion criteria. The findings indicate that gamification significantly improves student motivation, participation, engagement, and learning outcomes in PAI learning. The most commonly used gamification forms include Quizizz, Kahoot, Wordwall, Gimkit, and educational game-based applications. Gamification was found to be more effective in procedural and conceptual materials, such as fiqh and Qur’an-Hadith learning, compared to value-oriented materials such as morals and faith. In conclusion, digital gamification has strong potential as an innovative learning strategy in Islamic education; however, a more integrative and values-oriented design is required to support comprehensive character formation.